1997
DOI: 10.1155/1997/538754
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cylindrical Shells Using Generalized Differential Quadrature

Abstract: The analysis of cylindrical shells using an improved version of the differential quadrature method is presented. The generalized differential quadrature (GDQ) method has computational advantages over the existing differential quadrature method. The GDQ method has been applied in solutions to fluid dynamics and plate problems and has shown superb accuracy, efficiency, convenience, and great potential in solving differential equations. The present article attempts to apply the method to the solutions of cylindri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
68
1
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(87 citation statements)
references
References 5 publications
14
68
1
4
Order By: Relevance
“…r=E p of a simply supported empty cylinder are compared with the solution derived using generalized differential quadrature method (DQM) by Loy et al [2] as shown in Table 1. They are varied with circumferential wave mode, n for axial wave number m = 1.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…r=E p of a simply supported empty cylinder are compared with the solution derived using generalized differential quadrature method (DQM) by Loy et al [2] as shown in Table 1. They are varied with circumferential wave mode, n for axial wave number m = 1.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In Figure 6 From the previous data, the shell frequencies are affected highly as the fluid quantities [11,[31][32][33][34][35] and ring supports are appended [2,5,27,36]. A beam type vibration of CSs crops up when the addition of ring supports are made.…”
Section: Frequency Analysis Of Empty and Fluid-filled Cylindrical Shementioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 shows the comparison of the variation of frequency parameter of isotropic cylindrical shells with circumferential wave number n and h/R ratio to that of Loy et al [33] for simply-supported end condition having shell parameters (m = 1, L/R = 20). In Table 3, comparison of natural frequencies (Hz) for simply-supported type I and type II FGM cylindrical shell is made with Loy et al [6] against circumferential wave number n for various Tables 4, 5, and 6, variations of natural frequencies (Hz) against circumferential wave number n are given for types I & II FG cylindrical shells on elastic foundation.…”
Section: Resultsmentioning
confidence: 99%
“…* Ω kj -частота для k-й окружной и j-й осевой гармоники) для случая собственных колебаний цилиндрической оболочки с различными граничными условиями с данными из литературы [8,9,[11][12][13][14]. В табл.…”
Section: тип граничных условийunclassified